The Bioactivities of Seed Coat and Embryo Extracts from Indian Gooseberry (Phyllanthus emblica) - Jaiboonma, A.; Janvikul, W.; Poeaim, S. (International Journal of Agricultural Technology, 2018)
The research evaluated the bioactivities of seed coat and embryo extracts from Indian gooseberry (Phyllanthus emblica Linn). The crude methanolic extract was further successively extracted with hexane, ethyl acetate, n-butanol and water by liquid-liquid partitioning method. The total phenolic content (TPC) in each solvent-extracted fraction was determined by Folin-Ciocateu method. The ethyl acetate seed coat extract possessed the highest TPC with values of 439.09±5.49 milligrams gallic acid equivalent (mgGAE)/g extract. The antioxidant activity of each extract was examined using ferric-reducing antioxidant power (FRAP) and 2, 2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS•+) assay. The ethyl acetate seed coat extract revealed 50% inhibitory concentration (IC50 value) at a concentration of 31.53±0.36 microgram/milliliter (µg/ml) and ferric-reducing antioxidant power with 751.92±5.22 milligrams ascorbic acid equivalent (mgAAE)/g extract. The antibacterial activity of each extract was performed using disc diffusion method. The ethyl acetate seed coat extract demonstrated the greatest bacterial inhibition against Bacillus subtilis ATCC 6633, Bacillus cereus DMST 5040, Staphylococcus epidermidis ATCC 12228, Staphylococcus aureus TISTR 1466, and Micrococcus luteus ATCC 9341. These results suggested that the seed coat extracted with ethyl acetate could be served as a natural source of the bioactive compounds and used in the preparations of products such as drugs, anti-aging supplements, and cosmetics.